Double Lacunary Statistical Convergence of Order \(α\) in Topological Groups via Ideal - Savas, Ekrem (Communications in Mathematics and Applications, 2018)
Recently, \(I\)-lacunary double statistical convergence in topological groups is presented by Savas [31]. In this paper, we extend the concepts of \(I\)-double statistical convergence and \(I\)-double lacunary statistical convergence to the concepts of \(I\)-double statistical convergence and \(I\)-double lacunary statistical convergence of order \(α\), \(0 <α ≤ 1\). We also investigate some inclusion relations between \(I\)-double statistical of order \(α\) and \(I\)-double lacunary double statistical convergence of order \(α\).